2021
DOI: 10.1071/mf20022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of swimming net material on populations of an endangered seahorse

Abstract: The endangered seahorse Hippocampus whitei has declined in abundance as a result of natural habitat loss, and inhabits copper-braided protective swimming nets in Sydney Harbour, Australia. This study tested whether the use of copper-free seahorse-friendly net material has any effect on populations of H. whitei. The effects of net material on seahorse density and population abundance, as well as the effects on fouling epibiota and the abundance of epifaunal seahorse prey, were tested on pre-existing swimming ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Whilst habitats have declined across its range, H. whitei has shown an ability to adapt by utilising artificial habitats such as protective swimming nets (Hellyer et al, 2011;Simpson et al, 2021a;Simpson et al, 2021b) and purposefully designed artificial habitats known as seahorse hotels (Simpson et al, 2020). It was recently shown that adult H. whitei select artificial habitats over natural habitats (Simpson et al, 2019), similar to that of the only other Endangered seahorse species, Hippocampus capensis in South Africa (Claassens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst habitats have declined across its range, H. whitei has shown an ability to adapt by utilising artificial habitats such as protective swimming nets (Hellyer et al, 2011;Simpson et al, 2021a;Simpson et al, 2021b) and purposefully designed artificial habitats known as seahorse hotels (Simpson et al, 2020). It was recently shown that adult H. whitei select artificial habitats over natural habitats (Simpson et al, 2019), similar to that of the only other Endangered seahorse species, Hippocampus capensis in South Africa (Claassens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%